Electricity generation and consumption in Iran and the role of nuclear power for sustainable energy / Afshin Mazandarany - Afshin, Mazandarany (2012)
Over the years, the consumption of all types of energy, such as electricity, have increased rapidly in Iran. The economic growth of the country depends on electricity, and, therefore, the trend of electricity consumption is likely to keep growing in the future to sustain this growth. In view of this need, the government plans to build many new power plants and decided to redevelop its nuclear program to meet the rising electricity demand and decrease the consumption of fossil fuels. In this study, the effect of this policy on four major aspects of energy sustainability, including environmental pollution, electricity demand, energy security and electricity price have been verified. A clear view of 43 years of the evolutionary trend of the country’s power sector, has been shown by gathering data, including the capacity installed, electricity generated and amount of fossil fuel used from the years 1967 to 2009. In addition, the future power plant composition for Iran is investigated, and the fuel consumption and emissions predicted until 2025. In recent decades, thermal power plants generated about 94% of electricity and about 6% was generated by renewable sources such as hydropower. If the dominance of new power plants is by thermal type, the CO2 and other air pollutant emissions will increase. The results show that increasing the share of renewable sources and the construction of 20,000 MW nuclear reactors will reduce 26% of hazardous CO2 emissions into the environment; nevertheless, there are some other effective policies and technologies that can be implemented to control the emissions. In respect of answering the country’s growth rate for energy demand, which is very high, neither nuclear nor fossil fuels can cope with the current growth. Therefore, the only solution is rationalizing the energy demand and controlling energy wastage by encouraging energy efficiency. v In the field of energy security, although Iran has huge oil and gas reserves, it faces many threats. The major threats are the high growth rates of energy consumption, economic dependency on crude oil exports, wastage of energy, lack of attention to common fossil fuel resources and political conflict. Therefore, the energy policy must be reformed to address these problems rather than investing in nuclear facilities. To investigate the relative cost of electricity generated in each alternative generator, the simple levelized electricity cost was selected as a method. The results show that in the country’s current circumstances, the electricity cost in fossil fuel power plants will be cheaper than nuclear. In conclusion, although nuclear energy, including its fuel cycle is Iran’s assured right, constructing more nuclear power plants will not solve the energy sustainability problems. In fact, it may be the catalyst for deterioration since it will divert capital and other finite resources from top priority and economic projects such as energy efficiency, high-technology development and energy resources management.